Initial supplementary dose of dolutegravir in second-line antiretroviral therapy: a noncomparative, double-blind, randomized placebo-controlled trial - Zhao, Y; Griesel, R; Omar, Z; Simmons, B; Hill, A; van Zyl, G; Keene, C; Maartens, G; Meintjes, G (Oxford University Press, 2023)
Background: Dolutegravir concentrations are reduced by efavirenz induction effect necessitating twice-daily dolutegravir dosing when coadministered. Efavirenz induction persists for several weeks after stopping, which could potentially select for dolutegravir resistance if switching occurred with unsuppressed human immunodeficiency virus type 1 (HIV-1) RNA levels and standard dolutegravir dosing. We evaluated the need for a lead-in supplementary dolutegravir dose in adults failing first-line tenofovir-emtricitabine-efavirenz (TEE).